Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation \(\log x + \log (x - 1) = \log 90\), follow these steps:
1. Combine the logarithmic terms on the left side of the equation:
Recall the property of logarithms that states \(\log a + \log b = \log (a \cdot b)\). Using this property, we can combine the terms on the left side:
[tex]\[ \log x + \log (x - 1) = \log (x \cdot (x - 1)) \][/tex]
2. Rewrite the equation:
Substitute \(\log (x \cdot (x - 1))\) back into the equation:
[tex]\[ \log (x \cdot (x - 1)) = \log 90 \][/tex]
3. Equate the arguments of the logarithms:
Since the logarithm function is one-to-one, if \(\log A = \log B\), then \(A = B\). Therefore, we can write:
[tex]\[ x \cdot (x - 1) = 90 \][/tex]
4. Solve the resulting quadratic equation:
Expand and set the equation to zero:
[tex]\[ x^2 - x - 90 = 0 \][/tex]
This is a standard quadratic equation of the form \(ax^2 + bx + c = 0\).
5. Factor the quadratic equation:
Find two numbers that multiply to \(-90\) and add to \(-1\). These numbers are \(-10\) and \(9\). Thus, we can factor the quadratic equation as:
[tex]\[ (x - 10)(x + 9) = 0 \][/tex]
6. Solve for the roots:
Set each factor to zero and solve for \(x\):
[tex]\[ x - 10 = 0 \quad \text{or} \quad x + 9 = 0 \][/tex]
[tex]\[ x = 10 \quad \text{or} \quad x = -9 \][/tex]
7. Check for extraneous solutions:
Since \( \log x \) and \( \log(x-1) \) are only defined for positive values of \(x\) and \(x-1 > 0\), we need \(x > 1\). Therefore, the solution \(x = -9\) is not valid because it does not satisfy the domain constraint.
The valid solution is:
[tex]\[ x = 10 \][/tex]
Therefore, the solution to the equation \(\log x + \log (x - 1) = \log 90\) is:
[tex]\[ \boxed{10} \][/tex]
1. Combine the logarithmic terms on the left side of the equation:
Recall the property of logarithms that states \(\log a + \log b = \log (a \cdot b)\). Using this property, we can combine the terms on the left side:
[tex]\[ \log x + \log (x - 1) = \log (x \cdot (x - 1)) \][/tex]
2. Rewrite the equation:
Substitute \(\log (x \cdot (x - 1))\) back into the equation:
[tex]\[ \log (x \cdot (x - 1)) = \log 90 \][/tex]
3. Equate the arguments of the logarithms:
Since the logarithm function is one-to-one, if \(\log A = \log B\), then \(A = B\). Therefore, we can write:
[tex]\[ x \cdot (x - 1) = 90 \][/tex]
4. Solve the resulting quadratic equation:
Expand and set the equation to zero:
[tex]\[ x^2 - x - 90 = 0 \][/tex]
This is a standard quadratic equation of the form \(ax^2 + bx + c = 0\).
5. Factor the quadratic equation:
Find two numbers that multiply to \(-90\) and add to \(-1\). These numbers are \(-10\) and \(9\). Thus, we can factor the quadratic equation as:
[tex]\[ (x - 10)(x + 9) = 0 \][/tex]
6. Solve for the roots:
Set each factor to zero and solve for \(x\):
[tex]\[ x - 10 = 0 \quad \text{or} \quad x + 9 = 0 \][/tex]
[tex]\[ x = 10 \quad \text{or} \quad x = -9 \][/tex]
7. Check for extraneous solutions:
Since \( \log x \) and \( \log(x-1) \) are only defined for positive values of \(x\) and \(x-1 > 0\), we need \(x > 1\). Therefore, the solution \(x = -9\) is not valid because it does not satisfy the domain constraint.
The valid solution is:
[tex]\[ x = 10 \][/tex]
Therefore, the solution to the equation \(\log x + \log (x - 1) = \log 90\) is:
[tex]\[ \boxed{10} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.